TEACHER’S PERCEPTION ON BUILDING CHARACTER BY INTEGRATING ISLAMIC VALUES INTO FOREIGN LANGUAGE LESSON IN INDONESIAN CONTEXT - Yulmiati Yulmiati; Vivi Indriyani; M Zaim; Syahrul Ramadhan; Agustina Agustina (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
Indonesia grows in relation to Islamic values in daily life, because Islam is the dominant religion in this country. Based on these conditions, in education Islamic values are important to be instilled by teachers into the lesson, because they can build good character for students. This article aims at discussing teachers’ perception about the integration of Islamic values foreign language learning in Indonesian context. A descriptive study with a questionnaire collection technique was used in this research. A questionnaire sheet was developed via google form and distributed through the WhatsApp   group of English subjects teacher association (MGMP) in West Sumatera. The questionnaire was responded to by 70 (seventy) teachers. The results showed that the teachers want to integrate Islamic values in teaching material. However, the teaching materials that contain it are not easy to find. Then, the teachers also perceived that integrating Islamic values into teaching learning process can build student character.